2010
DOI: 10.1103/physreve.82.021605
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field-crystal dynamics for binary systems: Derivation from dynamical density functional theory, amplitude equation formalism, and applications to alloy heterostructures

Abstract: The dynamics of phase field crystal (PFC) modeling is derived from dynamical density functional theory (DDFT), for both single-component and binary systems. The derivation is based on a truncation up to the three-point direct correlation functions in DDFT, and the lowest order approximation using scale analysis. The complete amplitude equation formalism for binary PFC is developed to describe the coupled dynamics of slowly varying complex amplitudes of structural profile, zerothmode average atomic density, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 92 publications
1
93
0
Order By: Relevance
“…Thus, when q = 1 the phase transition is of second order for r > −9/38 and of first order for r < −9/38. As already mentioned, this result is exact in the sense that it is unchanged if more modes are included in the ansatz (11) and improves on the prediction r = −1/4 obtained for the PFC model using a one-mode approximation [2]. Note that the vacancy term (5) does not affect the transition because φ is positive everywhere.…”
Section: Equation (13) Then Yieldssupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, when q = 1 the phase transition is of second order for r > −9/38 and of first order for r < −9/38. As already mentioned, this result is exact in the sense that it is unchanged if more modes are included in the ansatz (11) and improves on the prediction r = −1/4 obtained for the PFC model using a one-mode approximation [2]. Note that the vacancy term (5) does not affect the transition because φ is positive everywhere.…”
Section: Equation (13) Then Yieldssupporting
confidence: 81%
“…This interpretation is bolstered by the fact that it has been shown that the PFC model [Eqs. (1) and (2)] may be derived from the density functional theory of freezing [9] and the dynamical density functional theory for colloidal particles [10,11] with certain approximations. The free energy is minimized by either periodic structures or by a homogeneous flat profile, depending on the values of q, r, andφ =…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the spatial limitation of the standard PFC, in this work we will use an amplitude expansion of the density field [25][26][27][28][29]. This methodology allows the study of 2D films adsorbed on a rigid substrate with spatial dimensions of several hundred nanometers, yet retains atomistic resolution.…”
mentioning
confidence: 99%
“…This periodic variation limits the applicability of the model as the grid spacing must be less than the atomic spacing. To overcome this difficulty, an amplitude expansion was developed by Goldenfeld et al [25][26][27][28][29]. In this formulation the density is expanded around the basis set as the substrate, i.e., n ¼ P j e iG s j Ár þ c:c:, where j is a complex amplitude that varies on length scales much larger than 2=jG …”
mentioning
confidence: 99%
See 1 more Smart Citation